The Correlation Between Students' Formal Thinking Skills And The Capability To Solve Chemistry Olympiad Problems - Said Ali Akbar, (Jurnal Serambi Ilmu, 2024)
This research aimed to determine the relationship the relationship formal thinking skills of chemistry olympiad participants with problem solving skills the chemistry olympiad questions. The study population was all students from high school or MAN in Banda Aceh and Aceh Besar province participating in the Olympiad. The data was collected using a test instrument. In addition, interviews were also used as supporting data in the study. Processing quantitative data used Spearman rank correlation coefficient, while qualitative in percentage form. The results of the analysis obtained rs value about 0,94. Check the table of values ​​r product moment with df of 14, at a significance level of 5% is obtained r table = 0,532, whereas the significance level of 1% is obtained r = 0,661 table. rs value is greater than the price r table, both at significance level of 5% (0,94 > 0,532), as well as the significant level of 1% (0,94 > 0,661). Thus, the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the ability of formal influence Olympiad participants in solving problems.